Conversation takes two: understanding interactions with people with dementia. Issue 7 (9th August 2017) - Webb, Joseph
Abstract: The term 'person-centred' underpins dementia policy and approaches to support people with dementia. However, 'person-centredness' remains hazy, and words and definitions matter greatly when they are at the heart of defining what happens in people's lives. Drawing on data from an ongoing project, this article suggests that conversations which include a person with dementia can elucidate how 'relational' support is enacted in practice and the implications this can have on our understanding of 'person-centredness'. Identities are shaped in part through how we speak to people, and how they speak to us. This is particularly pertinent to the aims of 'person-centredness'. A conversation analytic approach to dementia support may therefore move us towards seeing 'personhood' as jointly constructed and reconstructed through interactions with others.